Design and Build PLTS On-Grid as Household-Scale Electricity Support - Aripriharta, Ari (Universitas 17 Agustus 1945 Jakarta, 2024)
At present the installation of PLTS in households is one of the government programs as stated in the Minister of Energy and Mineral Resources regulation No.49 of 2018 which contains permits for PLTS installation, independent electricity production and electricity export to PLN. Therefore, a Final Project was created with the title